1948
DOI: 10.1084/jem.87.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Scrub Typhus (Tsutsugamushi Disease)

Abstract: Although animals which recover from disease induced by one strain of Rickettsia tsutsugamushi are resistant to infection with heterologous strains (1-10), all organisms now grouped in this subgenus are not antigenically homogeneous. Evidence for heterogeneity is obtained in serological studies which employ complement fixation (11, 12), serum protection (13), and toxin-antitoxin techniques (14). Non-infectious vaccines of several types are capable of immunizing mice against the homologous strain of R. tsutsugam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1952
1952
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…In cross-vaccination or cross-immunization, mice or guinea pigs are immunized with either killed Orientia organisms or live organisms administered by a nonlethal route of inoculation, usually subcutaneously [40,79,111,112]. Immunized animals are subsequently challenged with dilutions of live homologous or heterologous strains.…”
Section: Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…In cross-vaccination or cross-immunization, mice or guinea pigs are immunized with either killed Orientia organisms or live organisms administered by a nonlethal route of inoculation, usually subcutaneously [40,79,111,112]. Immunized animals are subsequently challenged with dilutions of live homologous or heterologous strains.…”
Section: Cfmentioning
confidence: 99%
“…One important product of the research from the World War II era was the discovery of dramatic antigenic variation among strains of O. tsutsugamushi. This variation was shown using several methods available at the time, including cross-neutralization, cross-vaccination, or cross-immunization and complement fixation (CF) [40]. In addition to antigenic variation, research showed great interstrain variability in virulence in humans and rodents that ranged from unapparent disease to disease that was consistently fatal when untreated.…”
mentioning
confidence: 99%
“…Antigenic heterogeneity among strains of Rickettsia tsutsugamushi has been documented by the use of various techniques: (1) complement fixation (Bengtson, 1945(Bengtson, , 1946Shishido, 1964;Shirai and Wisseman , 1975); (2) cross-neutralization (Bell, Bennett and Whitman, 1946;Gauld , 1947, 1949;Fox, 1949;Miesse, Diercks and Danauskus, 1950;Plotnikova and Tarasevich , 1967); (3) toxin neutralization (Smadel et al, 1946); (4) cross-vaccination (Rights , Smadel and Jackson, 1948); and (5) immunofluorescence (Iida , Kawashima and Kawamura, 1965;Shirai and Wisseman, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Homologous protection developed from natural infection persists for at least one year, but heterologous protection may remain for less than six months. 19,20 Both humoral and cell-mediated immune responses are important in protective immunity against scrub typhus.…”
Section: Introductionmentioning
confidence: 99%